Detección de anticuerpos contra Babesia spp. en el perro Ganacho del bosque seco del sur del Ecuador. - Ochoa Torres, Carolina Daniela (2025)
In the Southern region of Ecuador, in the Dry Forest area of Loja, there is a presence of the native dog breed known as "Ganacho", which is considered a local genetic resource. This breed is characterized by its role in assisting goat herders with livestock management, which is the main economic activity in the region. Despite their significant importance, these dogs often lack proper care, which makes them susceptible to ectoparasites that transmit hemotropic diseases such as Babesia spp. These protozoa can cause various clinical outcomes, from mild or transient illness to acute or fatal infections. Currently, there is limited information regarding the health status of the "Ganacho" dog. For this reason, the present study is of great relevance, as it aims to determine the presence of antibodies against Babesia spp. and identify the associated risk factors. A non-probabilistic sampling was carried out by collecting blood samples from 70 dogs in different areas of the dry forest region in the Loja province. A 10 ml blood sample was obtained through venipuncture of the cephalic vein, and the samples were collected in Vacutainer tubes without anticoagulant to obtain serum. The samples were analyzed using the Indirect ELISA antigen-antibody technique. The results showed that 41.4% of the dogs tested positive for antibodies against Babesia spp. The highest seroprevalence was found in senior dogs (47%), with a higher frequency in females (43%) compared to males (40%), in medium-sized dogs (55%), those with dark-colored coats (57%), and a higher incidence was observed in the lower altitudinal zone (86%). The statistical analysis was performed using the Chi-square test, which revealed no statistically significant relationship (pvalue > 0.05) between the risk factors and the presence of antibodies, except for the altitudinal zone. This suggests that the altitudinal factor does influence the presence of the hemotropic parasite.